The Influence of Diversification on Innovative Activity in Regional Manufacturing Industry - Grebenkin, Igor Vladimirovich (Economy of Regions, 2018)
The study analyzes the relationship between the diversification of industry in its certain fields and characteristics of regional innovation systems. The relevance of this topic is due to a need to identify and verify the structural factors of sustainable development of the industry according to innovation scenarios. The study clarifies the methodological frameworks and the role of diversification as a factor of regional economic development. The purpose of the study is to assess the impact of diversification on innovative activity in the manufacturing industry. I present an empirical analysis of both the level of diversification of regional manufacturing industry and the selected indicators characterizing innovative activities. I define positive and negative trends of development. The level of diversification is characterized by high heterogeneity. It allows selecting the most and the least diversified regions. The analysis shows the significant regional difference in the level of innovative activity in the manufacturing industry, as well as in the share of the output of innovative products. On this basis, I assessed the regions taking into account the dynamics and the level of innovative activity in the manufacturing industry. The study has revealed a positive relationship between the level of diversification of manufacturing industry, innovative activity and the share of the output of high-tech products. This positive correlation is observed in all specifications and indicates the presence of externalities in industry development of the regions. The identified trends are more common for regions with a lower level of per capita gross domestic product. At the same time, I noted the limitations of using the diversification effects for the growth of innovative activity in the manufacturing industry. The results have both the theoretical and applied significance. Therefore, they may be applied when making strategic decisions related to the choice of directions for the territorial and sectoral development.